TO STUDY THE IMPLICATIONS OF VARIOUS PARAMETERS OF HANDWRITING OF AN INDIVIDUAL TO FIND HIS BEHAVIOUR AND SENTIMENT. - Nemane, Vandana Prashant; Kumar, Shailesh; Patil, Ranjit D. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Analyzing a person’s writing can provide important insights on their sentiment and behaviour by looking at a variety of linguistic and psychological factors. While lexical choices like pronouns and emotional or cognitive words reveal the writer’s focus and social orientation, sentiment polarity—whether positive, negative, or neutral—highlights the emotional tone. Punctuation, sentence structure, and complexity provide more information on cognitive processes and emotional intensity. The use of metaphors and images, as well as temporal attention, reveal the inner condition and concerns of the individual. Additional factors that influence behavioural patterns like assertiveness, anxiousness, or self-focus include tone, repetition, and psycholinguistic traits. Through the integration of these criteria, text analysis provides a window into an individual’s psychological composition and is an effective tool for recognizing emotional states, cognitive tendencies, and possible behaviours.